Simulation of Water Tree Defect on Different Types of XLPE Underground Power Cable Using Finite Element Analysis - Yanuar Zulardiansyah, Arief; Hendri, Masdi; Kelvin Juing, Tinggom; Aulia, Aulia; Irza, Sukmana; Rosyid Ridlo, Al Hakim (2022)
An investigation of a different type of polymeric underground power, namely cross-linked polyethylene (XLPE) type cable is described in this paper. The investigation is performed based on the effect of the water tree defects. The finite element technique was employed in this work to observe the electric field distribution in the XLPE insulation part. The main water tree defects of this work, namely vented and bow-tie water trees were selected. Each defect size was modeled and simulated, then the position of the defects is varying with regard to XLPE insulation and cable conductor. The rated voltage was varied according to the cable type in order to observe the electric field distribution profiles. The IEC 60502-2 Standard is consistently referred to make design and model the XLPE power cable. It was found that the bow-tie water tree has less electric field intensity profile compared with the effect of the vented water tree.